Bioecology and Development of California Scale (Quadraspidiotus Perniciosus Comst.) in Uzbekistan - N. D, Makhmudova (American Journal of Biodiversity, 2024)
It is widely used in Uzbekistanare commondangerous coccids. Among them is the quarantine pest Californian scale. It damages many plants. It damages apple, pear, plum, quince, peach, almond, hawthorn, elm, poplar and others. It overwintersdiapausingfirst-stage larvae covered with a dark gray or black shield. In the spring, it feeds intensively, molts and forms a shield similar to that of an adult female. After the second molt, adult females are formed. After mating, the femalesgives birthlarvae-vagrants, which crawl along branches and leaves, and can also settle on fruits. It gives rise to the next generation.